Warm white emission property of Ca2Sr(PO4)2:Dy3+ phosphors with red compensation by Eu3+ co-doping. Issue 2 (1st February 2018) - Yu, Meng; Zhang, Wentao; Yan, Guilin; Dai, Siyi; Qiu, Zeliang; Zhang, Li
Abstract: A series of Ca2 Sr(PO4 )2 :Dy 3+, Eu 3+ phosphors was synthesized via a solid-state reaction, and Eu 3+ is co-doped in Ca2 Sr(PO4 )2 :Dy 3+ for warm white emission through a red light compensation. The structure and luminescence properties of these samples were investigated. X-ray diffraction indicated that the characteristic structure of Ca2 Sr(PO4 )2 was unchanged after doping with Dy 3+ and Eu 3+ . Under excitation at 353 nm, the Dy 3+ -doped Ca2 Sr(PO4 )2 phosphors emitted a white light that contained contributions from blue (488 nm) and yellow (580 nm) emissions, which corresponded to the 4 F9/2 → 6 H15/2 and 4 F9/2 → 6 H13/2 electronic transitions of Dy 3+, respectively. Compared to Ca2 Sr(PO4 )2 :Dy 3+, the Ca2 Sr(PO4 )2 :Dy 3+, Eu 3+ phosphors exhibited an improved white-light luminescence with a red emission supplement, and excellent warm white light was obtained according to the chromaticity coordinates. The prepared Ca2 Sr(PO4 )2 :Dy 3+, Eu 3+ phosphor has potential applications as a single-component phosphor in white light-emitting diodes.